(untitled) (Interdisciplinary Studies Journal, 2025)
Grounded in Social Psychology and Social Constructionism, this study analyzed the meanings attributed to masculinities circulating among young male students in a public high school in the agreste region of Pernambuco, Brazil. The specific objectives were: to map the (co)produced meanings of masculinities based on conversation circles with students, and to analyze the linguistic repertoires linked to their everyday experiences. Employing a qualitative approach and anchored in a constructionist perspective, the research adopted conversation circles as a methodological device to promote the co-construction of meaning through dialogical interaction. The findings were organized into three analytical axes: processes of subjectivation, effects of the norm, and ruptures with the law. The study observed that the students negotiated their processes of subjectivation concerning masculinity in relation to prevailing social and cultural norms, demonstrating critical reflections on gender roles. Although hegemonic discourses remain present, tensions and (re)significations of masculinities are emerging, especially through more equitable and respectful practices. The study concludes with a call for urgent educational policies that incorporate discussions on gender and masculinities in schools, contributing to the transformation of what it means to be a man among young Brazilians.